Settlement of Juvenile Offenses in Klitih Cases Through Restorative Justice - Muhammad Satriyo Pramudita; Aidul Fitriciada Azhari (JUSTISI, 2025)
Klitih is a form of street violence committed by teenagers in Yogyakarta and is a serious concern. This research aims to analyze the application of restorative justice in the settlement of juvenile crime in klitih cases. The research approach used is normative juridical and empirical juridical, with primary data in the form of interviews and observations, as well as secondary data which includes legal documents and case reports. The results showed that the application of restorative justice can provide rehabilitation for the perpetrator and facilitate social reintegration, while restoring the victim's condition through the mediation and negotiation process. This process increases the offender's understanding of the impact of their actions, fosters responsibility, and builds empathy. However, the implementation of restorative justice faces obstacles, such as limited resources, community stigma towards offenders, and law enforcement skepticism towards the effectiveness of this method compared to the conventional punishment system. This research offers a new contribution by highlighting the unique sociocultural dynamics of Yogyakarta that influence the effectiveness of restorative justice in klitih cases. In addition, it provides policy recommendations, including community involvement in community-based programs and culturally sensitive training for facilitators. The conclusion of this study confirms that restorative justice has significant potential to effectively address juvenile delinquency, provided it is supported by training, adequate facilities, legal reforms, and strategies that are adaptive to the social and cultural context.